Temperature-dependent structural, optical, and electrical performance assessment of fabricated (Au, Al)/ZnO/p-Si heterojunction Schottky diodes - Rajoriya, Manisha; Sahni, Mohit; Singh, Munendra; Singh, Sucheta; Gupta, Pallavi; Yahya, M. Z.A.; Noor, I. M. (John Wiley and Sons, 2025)
This work incorporates the fabrication and characterization of highly transparent zinc oxide (ZnO) film deposited on p-type Si (100). The work also includes the temperature dependency of fabricated (Au, Al)/ZnO/p-Si-heterojunction Schottky diodes. This temperature analysis is done in terms of optical, structural, and electrical analysis. The fabrication of the proposed sample has been carried out using RF magnetron sputtering and then sintered at two different temperatures (100 °C and 300 °C). Structural properties of these films are analyzed and compared using XRD, SEM, and AFM. Further, this work explores the electrical properties of various types of Schottky junctions fabricated with gold and aluminum metal contacts on these thin films. With the increasing fabrication temperature, both the optical band gap as well as the ideality factor are found to be decreasing. The impact of temperature variation on the potential barrier of Schottky diodes and carrier concentration has also been studied. This work and device fabrication have applications in the field of analog circuits and electronics.